2015
DOI: 10.1111/febs.13355
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into N‐terminal to C‐terminal interactions and implications for thermostability of a (β/α)8‐triosephosphate isomerase barrel enzyme

Abstract: Although several factors have been suggested to contribute to thermostability, the stabilization strategies used by proteins are still enigmatic. Studies on a recombinant xylanase from Bacilllus sp. NG-27 (RBSX), which has the ubiquitous (b/a) 8 -triosephosphate isomerase barrel fold, showed that just a single mutation, V1L, although not located in any secondary structural element, markedly enhanced the stability from 70°C to 75°C without loss of catalytic activity. Conversely, the V1A mutation at the same pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…1B). It must be noted that this surface pocket was not observed in the native RBSX structure (PDB code 4QCE) [23]. Analysis of atoms lining the surface pocket in 5EFD (chain A) and their atom-wise solvent accessibilities (ASA (Å 2 )) revealed that this surface pocket is composed of both polar and apolar atoms (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). It must be noted that this surface pocket was not observed in the native RBSX structure (PDB code 4QCE) [23]. Analysis of atoms lining the surface pocket in 5EFD (chain A) and their atom-wise solvent accessibilities (ASA (Å 2 )) revealed that this surface pocket is composed of both polar and apolar atoms (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Indexing and integration of all the X-ray data sets was carried out using iMOSFLM [43] followed by scaling and merging with AIMLESS [44] program in CCP4 program suite [45]. Molecular replacement method using the program Phaser-MR [46] from the CCP4 program suite, was used for structure solution with native RBSX structure (PDB code 4QCE) [23] as the search model. Automated model rebuilding and completion of the molecular replacement solution was carried out using Phenix AutoBuild Wizard which uses RESOLVE, xtriage and phenix.refine to build an atomic model, refine it, and improve the same with iterative density modification, refinement, and model building [47].…”
Section: Methodsmentioning
confidence: 99%
“…An in silico analysis of a set of two-state folding proteins showed the presence of an N-C motif (N-terminal to C-terminal contacts) and suggested its possible role in initial protein folding, native state stability and final turnover [19]. In a recent study, we have provided experimental evidence through crystal structure analysis of different extreme N-terminus aliphatic mutants of RBSX where augmenting N-terminal to C-terminal interactions is associated with enhancement of the stability of the enzyme [11]. The present results are consistent with earlier findings and exemplify the importance of interactions between N-terminus and C-terminus specifically through aromatic interactions and provide a network perspective of aromatic interactions/cluster in modulating the stability of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…RBSX is a monomeric GH10 xylanase having (β/α) 8 -TIM barrel fold [11]. The native structure of RBSX is composed of twelve α -helices, nine β -strands and five 3 10 -helices, as assigned by DSSP [12].…”
Section: Structural Features Of Phe4-trp6-tyr343 Aromatic Cluster In mentioning
confidence: 99%
See 1 more Smart Citation